French Encounters Of François De La Boullaye-Le Gouz In India: Hindu Mythological Illustrations and Narratives. (22nd June 2022) - Kundra, Sakul; Sinha, Arvind; Sarwal, Amit
Seventeenth-century French travellers' records ignited the curiosity of the Occidental world, especially the French imagination, because of their commercial and religious understanding of the Orient, mainly India. Among their authors, the most unresearched traveller is François de la Boullaye-le Gouz, who wrote a fabulous account about his voyage to India. His understanding of the Hindu religion ideologies and pictorial representations require analysis based on this hitherto unused manuscript. This article examines the distorted and under-researched facts about his biography, followed by scrutinizing Gouz's perceptions of Hindu gods and goddesses and their significance in Hindu mythology. These observations, interpretations and misrepresentations of Hindu religious illustrations through Gouz's perception are analyzed by examining printed French untranslated memoirs (printed in 1653) in comparison with Gouz's abridged manuscript (codex). Varied approaches of scholars such as Subrahmanyam, Sapra, Beasley, Marsh, Dew and Teltscher have criticized Said's Orientalism. Our research contributes fresh insight by undertaking an in-depth comparative study of this Oriental knowledge (Gouz' Hindu mythology observations) with Oriental records, his narratives and codex. This ascertains the credibility of knowledge that formulated French's Oriental image of India in early-modern Europe.